2021
DOI: 10.3389/fmolb.2021.790091
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Glycemic Level on the Salivary Proteome of Middle-Aged and Elderly People With Type 2 Diabetes Mellitus: An Observational Study

Abstract: Type 2 diabetes mellitus (T2DM) is an increasing global public health concern, but its impact on the salivary proteome is still unclear. To evaluate the effect of glycemic levels in middle-aged and elderly individuals with T2DM on salivary proteomics, we compared the differences by liquid chromatography tandem mass spectrometry (LC–MS/MS). Unstimulated whole saliva samples from 8 T2DM patients with good glycemic control (G group, HbA1c <6.5%) and 16 patients with poor control (P group, HbA1c ≥6.5%) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…Furthermore, patients with diabetes showed higher propensity to have reduced level of these proteins when compared to the control group. This finding is in agreement with a previous study where 40 different salivary proteins were found to be significantly affected by patients´ glycaemic control [ 36 ]. This is particularly important in reiterating the role of glycaemic control in mitigating adverse oral complications that are generally associated with diabetes mellitus as evidence by scientific reports [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, patients with diabetes showed higher propensity to have reduced level of these proteins when compared to the control group. This finding is in agreement with a previous study where 40 different salivary proteins were found to be significantly affected by patients´ glycaemic control [ 36 ]. This is particularly important in reiterating the role of glycaemic control in mitigating adverse oral complications that are generally associated with diabetes mellitus as evidence by scientific reports [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…27 An observational study evaluating the effect of glycemic levels in middle-aged and elderly individuals with T2DM on salivary proteomics by liquid chromatography tandem mass spectrometry (LC-MS/MS) showed FAM3D a key candidate protein and one of the three proteins with the best differentiation, which combined with thioredoxin domain-containing protein 17 (TXNDC17), zymogen granule protein 16B (ZG16B), and yielded an area under the curve (AUC) of 0.917 to distinguish good glycemic control and poor control. 28 In addition, FAM3D inhibited glucagon secretion via DUSP1-dependent suppression of ERK1/2 signaling. Though there were no researches on glucagon and ZFP36, the expression of ZFP36 can be down-regulated by overexpression of DUSP1, 12 and the up-regulated ZFP36 was proved to be related to lipid metabolism.…”
Section: Discussionmentioning
confidence: 98%
“…Studies also revealed that FAM3D promoted liver adipogenesis and gluconeogenesis by inhibiting the activity of Akt and AMPK and activating the adipogenic pathway, and FAM3D could inhibit glucagon secretion 27 . An observational study evaluating the effect of glycemic levels in middle‐aged and elderly individuals with T2DM on salivary proteomics by liquid chromatography tandem mass spectrometry (LC–MS/MS) showed FAM3D a key candidate protein and one of the three proteins with the best differentiation, which combined with thioredoxin domain‐containing protein 17 (TXNDC17), zymogen granule protein 16B (ZG16B), and yielded an area under the curve (AUC) of 0.917 to distinguish good glycemic control and poor control 28 . In addition, FAM3D inhibited glucagon secretion via DUSP1‐dependent suppression of ERK1/2 signaling 7 .…”
Section: Discussionmentioning
confidence: 99%
“… Malipatil et al (2019) quantified insulin growth factor, vitamin D binding proteins, and HbA1C using DIA-MS to predict the effect of diet and exercise on weight loss and insulin sensitivity. Salivary proteomics of diabetic patients identified TXNDC17, ZG16B, and FAM3D as novel biomarkers of hyperglycemia and oral disease in DM2 patients with poor glycemic control ( Jia et al, 2021 ). An MS-DIA based proteomic analysis of infected root canals of DM2 patients identified fortythree overexpressed proteins, the majority of which were related to immune-inflammatory response ( Loureiro et al, 2022 ).…”
Section: Immunoproteomics As Novel Diagnostic and Prognostic Toolmentioning
confidence: 99%